Managing knowledge, dynamic capabilities, innovative performance, and creating sustainable competitive advantage in family companies: A case study of a family company in Indonesia - Sugiarto Koentjoro; Sri Gunawan (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Family businesses often face significant challenges while trying to develop and increase their sustainability throughout generations. This is often due to their inability to properly manage the knowledge required to develop their resources to increase sustainability. Therefore, this study examines the relationship between processes of managing knowledge, dynamic capabilities, and innovative performance in an Indonesian family company in order to improve business performance. This is qualitative research with a single case study used to obtain data from nineparticipants in an Indonesian family company ("Ardiles") that focuses on footwear. The findings showed that a family company that mobilizes knowledge can improve its members' dynamic capabilities for proper business management and growth. Furthermore, the frequent process of mobilizing knowledge improves family members' dynamic capabilities to create new ideas. This creative process helps to improve its innovative performance, thereby creating a sustainable competitive advantage among family companies.
Keywords: 650; family company; managing knowledge; dynamic capability; entrepreneurial orientation; open innovation